2010
DOI: 10.5539/ijbm.v5n6p161
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Analysis of the Validity of Wagner’s Law in China A Case Study Based on Gibbs Sampler

Abstract: This paper presents an empirical analysis on the relationship between the size of Chinese government, as measured by its annual spending, and the growth rate of the economy. More specifically, it is designed to examine the applicability of Wagner's Law to the Chinese economy. The statistics used in this research are annual time series data on total government spending and gross domestic product covering the period of 1952 to 2007.Unexpectedly, our empirical results showed no strong evidence in support of the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 9 publications
1
3
0
1
Order By: Relevance
“…Using this technique, without considering structural breaks and using total government expenditure, Ziramba (2008) tentatively provides evidence in support of these results for South Africa by also concluding that there is no evidence of Wagner's law. Other studies using other techniques have also found similar results for various countries, some including South Africa (see, Ansari et al, 1997;Li, Li, Wang & Zheng, 2010). On the bottom block of table 8, E and G are found to be causing Y since the null of no Granger causality is rejected at the 5% of significance.…”
Section: Cointegrationsupporting
confidence: 60%
“…Using this technique, without considering structural breaks and using total government expenditure, Ziramba (2008) tentatively provides evidence in support of these results for South Africa by also concluding that there is no evidence of Wagner's law. Other studies using other techniques have also found similar results for various countries, some including South Africa (see, Ansari et al, 1997;Li, Li, Wang & Zheng, 2010). On the bottom block of table 8, E and G are found to be causing Y since the null of no Granger causality is rejected at the 5% of significance.…”
Section: Cointegrationsupporting
confidence: 60%
“…Zheng et al [19] studied the empirical analysis on the relationship between the size of Chinese government, as measured by its annual spending, and the growth rate of the economy. More specifically, it designed to examine the applicability of Wagner's law to the Chinese economy.…”
Section: Empirical Studiesmentioning
confidence: 99%
“…One problem with Tobin's analysis, however, is that he employed OLS regressions and did not pre-test the stationarity of the data, thus raising the possibility of spurious results. More recently, Afzal and Abbas (2010) analyze the law for Pakistan during the period 1960-2007 and find little evidence in support of it; and Zheng et al (2010) carry out an empirical analysis of the law in China and find no strong evidence in favor of it.…”
Section: Wagner's Hypothesis and Previous Testsmentioning
confidence: 99%
“…2 Refer, for instance, to works by Abizadeh and Gray (1985), Vatter and Walker (1986), Afxentiou and Serletis (1991), Yousefi and Abizadeh (1992), Ahsan et al (1996), Thornton (1999), and Florio and Colautti (2005), who find supporting evidence for Wagner's Law in various developed countries. 3 Works in this line include Diamond (1977), Abizadeh and Gray (1985), Ansari et al (1997), Halicioglu (2003), Akitoby et al (2006), Narayan et al (2008), Afzal and Abbas (2010), and Zheng et al (2010). 4 Not all of the studies analyzing the validity of Wagner Law in developing nations produce negative results.…”
Section: Introductionmentioning
confidence: 99%